Lipids and Neurotransmitters Mass Spectrometry Imaging Data from Dopaminergic PSAP Deficient (cPSAPDAT) and Serotonergic PSAP deficient (cPSAPSERT) Mice Brain Tissue sections - Kaya, Ibrahim; Nilsson, Anna; Shariatgorji, Reza; Andrén, Per (Uppsala University, 2025)
The files above are MALDI-MSI (Matrix Assisted Laser Desorption Ionization - Mass Spectrometry Imaging) experiments. The dataset contains both imzML, which is the common MSI open file type containing x, y positions in tissue as well as m/z and intensity, which is a more user friendly format. The data contained in this dataset should be enough to recreate the MSI parts of the manuscript.

Prosaposin (PSAP) modulates glycosphingolipid metabolism and may relate to Parkinson’s disease (PD). Here, the lipids and neurotransmitters MALDI-MSI data have been collected from dopaminergic PSAP-deficient (cPSAPDAT) mice and serotonergic PSAP-deficient (cPSAPSERT) mice as well as 6-OHDA-induced Parkinson's disease mouse model.

For any questions about the dataset or to request access to any files not uploaded here, please contact per.andren@uu.se
Keywords: Biomedical imaging; Medical and Health Sciences; Medicin och hälsovetenskap